Analysis of Government Internal Control System on Budget Implementation in Accordance with Government Regulation No 60 of 2008 - Hafit, Muhamad; Irianto, Gugus; Purwanti, Lilik (Journal of Accounting and Business Education, 2018)
This study aims to analyze the implementation of Government Internal Control System (SPIP) in the implementation of the budget at the Office of National Unity and Politics (Kesbangpol) Batu City with reference to PP No. 60 of 2008. This research is a qualitative research using descriptive approach and case study strategy.The results showed that the implementation of SPIP in the implementation of the budget in Kesbangpol Office still has not run maximally in accordance with PP Number 60 of 2008, this is indicated by the unfulfilled SPIP element as a whole. Among others: 1) No complete job description; 2) no mapping and documentation of risks impeding the implementation of SPIP; 3) there is no review on the performance of Kesbangpol Office; 4) information technology applications that are still not functioning maximally, and 5) Follow up monitoring by APIP that has not been paid attention maximally.